Extended spectrum beta‐lactamase and fluoroquinolone resistance genes and plasmids among Escherichia coli isolates from zoo animals, Czech Republic. Issue 3 (19th June 2013) - Dobiasova, Hana; Dolejska, Monika; Jamborova, Ivana; Brhelova, Eva; Blazkova, Lucie; Papousek, Ivo; Kozlova, Marketa; Klimes, Jiri; Cizek, Alois; Literak, Ivan
Abstract Commensal Escherichia coli isolates from healthy zoo animals kept in Ostrava Zoological Garden, Czech Republic, were investigated to evaluate the dissemination of extended‐spectrum beta‐lactamase (ESBL) and plasmid‐mediated quinolone resistance (PMQR) genes. A total of 160 faecal samples of various animal species were inoculated onto MacConkey agar with cefotaxime (2 mg L−1) or ciprofloxacin (0.05 mg L−1) to obtain ESBL‐ or PMQR‐positive E. coli isolates. Clonality of E. coli isolates was investigated by multilocus sequence typing and pulsed‐field gel electrophoresis. Plasmids carrying ESBL or PMQR genes were typed by PCR‐based replicon typing, plasmid multilocus sequence typing and restriction fragment length polymorphism. Forty‐nine (71%, n = 69) cefotaxime‐resistant and 15 (16%, n = 94) ciprofloxacin‐resistant E. coli isolates harboured ESBL or PMQR genes. Isolates were assigned to 18 sequence types (ST) and 20 clusters according to their macrorestriction patterns by pulsed‐field gel electrophoresis. The genes blaCTX‐M‐1 and qnrS1 were detected on highly related IncI1 plasmids assigned to clonal complex 3 (ST3, ST38) and on non‐related IncN plasmids of ST1 and ST3, respectively. The gene qnrS1 was located on related IncX1 plasmids. Dissemination of antibiotic resistance is associated with spreading of particular E. coli clones and plasmids of specific incompatibility groups among various animal species.